Linksnio kategorijos įsisavinimas: lietuvių kalba kaip gimtoji ir svetimoji - Savickienė, Ineta (Kalbotyra, 2006)
The main aim of this study is to determine the basic difference in ways Lithuanian category of case was mastered by native speaking children in their second-third year of age, and by adults whose native language is not Lithuanian. The data analysed was the errors and their interpretation that Lithuanian children and non-Lithuanian adults make in using nouns. The category of case is considered to be one of the most complex grammatical categories. This is due to several reasons: first, the category of case is morphological in form and syntactic in content; second, it enters into multiple oppositions. The use of prepositional phrases shows the tendency for prepositions to be omitted up to the age of two in children’s speech. Children prefare to use the premorpheme a instead of a preposition. The morphological case markers were acquired at an early age, but grammatically correct forms of a number of prepositions did not appear until the child was 3 years old. In contrast, non-Lithuanian adults used correct prepositions but the case forms caused difficulties for a long time. It can therefore be assumed that the correct form of case is acquired much earlier than prepositions by children but not by non-native adults.